ASAP: an automated system for scientific literature search in pubmed using web agentes - Carvalhal, Carlos (2013)
In this paper we present ASAP - Automated Search with Agents in PubMed, a web-based service aiming to manage and automate scientific literature search in the PubMed database. The system allows the creation and management of web agents, specifically parameterized thematically and functionally, that automatically and periodically crawl the PubMed database, oriented to search and retrieve relevant results according the requirements provided by the user. The results, containing the publications list retrieved, are emailed to the agent owner weekly during the activity period programmed for the web agent. The ASAP service is devoted to help researchers, especially from the field of biomedicine and bioinformatics, in order to increase their productivity, and can be accessed at: http://esa.ipb.pt/~agentes.